Control of the thymic medulla and its influence on αβT‐cell development. Issue 1 (May 2016) - Lucas, Beth; McCarthy, Nicholas I.; Baik, Song; Cosway, Emilie; James, Kieran D.; Parnell, Sonia M.; White, Andrea J.; Jenkinson, William E.; Anderson, Graham
Summary: The thymus is a primary lymphoid tissue that supports the generation of αβT cells. In this review, we describe the processes that give rise to the thymus medulla, a site that nurtures self‐tolerant T‐cell generation following positive selection events that take place in the cortex. To summarize the developmental pathways that generate medullary thymic epithelial cells (mTEC) from their immature progenitors, we describe work on both the initial emergence of the medulla during embryogenesis, and the maintenance of the medulla during postnatal stages. We also investigate the varying roles that receptors belonging to the tumor necrosis factor receptor superfamily have on thymus medulla development and formation, and highlight the impact that T‐cell development has on thymus medulla formation. Finally, we examine the evidence that the thymic medulla plays an important role during the intrathymic generation of distinct αβT‐cell subtypes. Collectively, these studies provide new insight into the development and functional importance of medullary microenvironments during self‐tolerant T‐cell production in the thymus.